COMPETENCY BASED ENGLISH TEACHING AND LEARNING (American Journal of Research in Humanities and Social Sciences, 2024)
Competency-based education has been gaining popularity as an approach to teaching and learning that focuses on developing skills and knowledge needed to succeed in the real world. English language teaching has also embraced this approach, as it seeks to prepare learners for the challenges of communication in a globalized world. This article discusses the concepts and principles of competency-based English language teaching and learning.